Keputusan Pembelian Konsumen Ditinjau dari Harga dan Brand Image pada Restorant Fastfood Mcdonald’s Jember - Fitrotullaili Aulina Rizqi; Yusita Titi Hapsari; Roro Aditya Novi Wardhani (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze the influence of price and brand image on consumer purchasing decisions at McDonald's fastfood restaurants in Jember Regency. This phenomenon is interesting because of the dynamics of modern lifestyles and global socio-political issues that influence consumer perceptions. The research method used is a quantitative approach by distributing questionnaires to 120 MCDonald's Jember customer respondents using a purposive sampling technique. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, and hypothesis tests (t-test and F-test). The results of the study partially show that price has a positive and significant effect on purchasing decisions (t=2.152; Sig.=0.033). The brand image variable also has a dominant and significant positive effect (t=10.363; Sig.<0.001). Simultaneously, both variables have a significant effect on purchasing decisions with a value of F=134.720 and a contribution of influence (R2) of 69.7%. These findings confirm that affordability through value-for-money packages and strong brand reputation are key factors for Jember consumers in choosing McDonald's as their primary culinary choice.